PENENTUAN TINGKAT KESULITAN TEKS BERDASARKAN PENGETAHUAN DUNIA SISWA - Nurul Shofiah; A. Syukur Ghazali; Nurchasanah Nurchasanah (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2016)
The aim of this study that describes the shape of the world's knowledge and comprehension levels of students, the text of which is based on knowledge of the world and the knowledge of the world's fifth grade students, as well as differences in students' understanding of towns and villages. This research data in the form of text that is already the world based on knowledge of internal and external students. The text of three text based world knowledge internal and external students, as well as the text of the outside world's knowledge of students. The results showed that the elementary fifth grade students from both schools were able to understand the meaning of vocabulary, linking vocabulary mapping into the meaning, composing paragraphs conclusion of the text that have been adapted to the students' knowledge of the world. Instead elementary fifth grade students from both schools are not able to understand the meaning of vocabulary, linking vocabulary mapping into the meaning, composing paragraphs of text that conclusion is not adapted to the students' knowledge of the world. So that the level of difficulty of the text that has been based on knowledge of the world is easy because it can help students understand the vocabulary in the text. Instead level of difficulty of the text that is not based knowledge of the students' world is difficult because students are not able to understand the meaning of the vocabulary that a textTujuan penelitian ini yakni mendeskripsikan bentuk pengetahuan dunia dan  tingkat pemahaman siswa, pada teks yang didasarkan pada pengetahuan dunia dan di luar pengetahuan dunia untuk siswa kelas V, serta perbedaan pemahaman siswa kota dan desa. Data penelitian  ini berupa teks yang sudah didasarkan pada pengetahuan dunia internal dan eksternal siswa. Teksnya berjumlah tiga teks  yang berdasarkan pengetahuan dunia internal dan eksternal siswa, serta teks yang diluar pengetahuan dunia siswa. Hasil penelitian menunjukkan bahwa siswa kelas V SD dari kedua sekolah mampu memahami makna kosakata, menghubungkan kosakata kedalam pemetaan makna, menyusun paragraf kesimpulan dari teks yang sudah disesuaikan dengan pengetahuan dunia siswa. Sebaliknya siswa  kelas V SD dari kedua sekolah tidak mampu memahami makna kosakata, menghubungkan kosakata kedalam pemetaan makna, menyusun paragraf kesimpulan dari teks yang tidak disesuaikan dengan pengetahuan dunia siswa. Sehingga tingkat kesulitan teks yang sudah didasarkan pengetahuan dunia yakni mudah karena dapat membantu siswa dalam memahami kosakata yang ada di dalam teks. Sebaliknya tingkat kesulitan teks yang tidak didasarkan pengetahuan dunia siswa yakni sulit karena siswa tidak mampu memahami makna kosakata yang ada pada teks